International Colloquium. Beyond Excavation. Geophysics, Aerial Photography and the Use of Drones in Eastern and South-East European Archaeology, 5–8 December 2016, Piatra-Neamț, Romania - Preoteasa, Constantin (Fundacja Rzeszowskiego Ośrodka Archeologicznego, 2017)
The paper presents several data on the international colloquium organized in 5–8 December 2016 to the Cucuteni Eneolithic Art Museum of Piatra-Neamț (Romania) by a Romanian- German joint research team, having as topic non-invasive interdisciplinary archaeological researches, especially geophysical surveys and aerial photographs made with drones. On this occasion were presented results of the profile investigations made especially during the last years in various historical and civilization sites, by scientists of the prestigious museums, universities and academic institutions from Romania, Germany, Poland, Republic of Moldova, Ukraine, Czech Republic, Hungary and Netherlands, through 22 presentations and 4 posters. These data are also included in the volume of abstracts of the event; currently the organizers are editing the volume with the proceedings of the colloquium.
Keywords: interdisciplinary archaeology; non-invasive surveys; geophysics prospections; aerial photography; drones; GIS; GPR; LiDAR